Breastfeeding Practice in Zhejiang Province, PR China, in the Context of Melamine-contaminated Formula Milk - Qiu, Liqian; Binns, Colin W; Zhao, Yun; Lee, Andy H; Xie, Xing (Journal of Health, Population and Nutrition, 2010)
A prospective cohort study of 1,520 mothers from Zhejiang province of China was undertaken to determine the duration of breastfeeding and associated factors during the first six months postpartum. Most (95.3%) mothers had introduced complementary foods by six months, making them at risk from contaminated infant formula. The mean duration of 'any breastfeeding' was greater than 180 days but only 48 days for 'exclusive breastfeeding'. Factors relating to cessation of any breastfeeding were maternal age, timing of the breastfeeding decision, admission of the infant to a special-care nursery, return of the mother to work, the early introduction of water and/or other complementary foods, and their location of residence. The introduction of infant formula before three months was positively associated with the late decision to breastfeed, births in city, and infants being given a prelacteal feed. To combat the melamine disaster, strategies to improve the duration of breastfeeding must be developed taking these factors into account. Key words: Breastfeeding; Cohort studies; Disasters; Exclusive breastfeeding; Melamine; Melamine disasters; Prospective studies; China DOI: 10.3329/jhpn.v28i2.4891 J Health Popul Nutr 2010 Apr; 28(2): 189-198